Is there a trade-off between academic research and faculty entrepreneurship? Evidence from U.S. NIH supported biomedical researchers - Dirk Czarnitzki; Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Is there a trade-off of scholarly research productivity when faculty members found or join for-profit firms? This paper offers an empirical examination of this question for a subpopulation of biomedical academic scientists who received research funding from the U.S. National Institutes of Health (NIH). In this study, we are able to distinguish between permanent versus temporary employment transitions by entrepreneurial faculty members and examine how their journal article publication rates change using individual-level panel data. We find that the biomedical scientists who eventually choose to found or join a for-profit firm were more productive during their careers in academe than a randomly selected control group of their NIH peers. When they pursue entrepreneurship in the private sector, however, their scholarly productivity falls. Those entrepreneurial faculty members who return to academe are not as productive as they were before their entrepreneurial experience in terms of journal publications.
Keywords: O38; O31; L53; 330; academic entrepreneurship; SBIR; NIH; biomedical research; life scientist productivity; Forschungskooperation; Unternehmer; Hochschulforschung; Industrielle Forschung; Medizin; Wissenschaftler; Publikationsanalyse; USA